DEVELOPMENT OF HANDOUTS WITH MAIN CONCEPTS AND MIND MAP ON STRUCTURE AND FUNCTION OF PLANT TISSUE FOR HIGH SCHOOL - Ika Anggraeni; Siska Arimadona (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2022)
Biology is a lesson full of concepts. The concepts contained in the subject matter tend to be memorized by students without interpreting them. One of the subject matter of biology is the structure and function of plant tissue. To help students understand the concepts contained in biology lessons, teaching materials are needed. One of the teaching materials that can be used is handouts. In addition, students also find it difficult to connect one concept to another, so they need to be helped with a mind map. Based on these problems, a handout that is equipped with the main concepts and a mind map on the structure and function of plant tissue material is developed that is valid and practical. This type of research is development research using 4-D models that have been modified into 3 stages, namely, define, design, develop and disseminate. Data were analyzed by descriptive statistical analysis. The results of the validity test show that this handout is valid in terms of didactic (84.52%), construction (85.94%) and technical (84.16%) aspects. The results of the practicality test of the handouts by teachers and students show that these handouts are practically used in the learning process. This shows that the handout which is equipped with the main concepts and a mind map on the material of the structure and function of plant tissue produced is valid and practical so that it can be used in learning biology in class XI schools.